Chinese yak and yellow cattle exhibit considerable differences in tissue content of squalene, tocopherol, and fatty acids. Issue 6 (22nd January 2015) - Liu, Chunyou; Jin, Guofeng; Luo, Zhang; Li, Shugang; Sun, Shuguo; Li, Yonggang; Ma, Meihu
<x xml:space="preserve">Abstract</x> Bioactive components in five tisues (longissimus muscle (LSM), biceps femoris muscle (BFM), liver (LV), subcutaneous adipose tissue (SAT), and abdominal adipose tissue (AAT)) of yak in Tibet and yellow cattle in Hubei were investigated. Yak was significantly higher (p<0.01) than yellow cattle in the squalene content of lipids of BFM (59.82/19.07 mg/100g), LSM (20.99/7.81 mg/100g) and LV (6.94/2.67 mg/100g), respectively, but not in SAT and AAT (p>0.05). Yak was also significantly higher (p<0.05) than yellow cattle in the total tocopherol content. Additionally, yak hepatic lipids showed the highest content of saturated fatty acids (58.11%) and polyunsaturated fatty acids (PUFA, 25.81%) and the lowest content of monounsaturated fatty acids (MUFA, 16.08%), while yellow cattle AAT had the highest content of MUFA (47.54%) and the lowest content of PUFA (2.36%). The considerable differences between the two in composition suggest that the five tissues of yak are potential sources of bioactive components and essential fatty acids for humans. Practical applications: The results from the analysis of the contents of squalene, tocopherols, total lipids，moisture, ash, and pH and fatty acid profile in the studied tissues of Tibet yak and Hubei yellow cattle provide useful information for developing functional foods using yak meat or other tissues as materials. <inline-graphic xlink:href="ark:/27927/pgjr0rr0zn" content-type="ejlt201400457-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Comparison of squalene and total tocopherol contents in different tissues of yak and yellow cattle.